Guía docente para la asignatura de Ciencias Naturales dirigida a Sexto Año de Educación Básica, fundamentada en el aprendizaje significativo - Gómez Torres, Jessica Beatriz (2015)
Natural Sciences comprise a set of disciplines that allow greater understanding of the world. In the sixth year of basic general education deepens conocimientodel ecosystem in the country, mainly on grasslands and various biomes. It also includes the study of climate, food chains, human nutrition and sexuality. This research proposes the creation of a teaching guide for this subject, based on meaningful learning, the learning theory was proposed by David Ausubel, which states that all new knowledge becomes meaningful for the learner when you can relate knowledge acquired above, strengthening the construction of cognitive structure. The research deals with the study of the physical, cognitive, emotional, social and language in students age 10 and corresponding curricular elements sixth year of basic general education foundations that support meaningful learning characteristics.